Effects of Guava (Psidium guajava L.) Leaf Extract on the Metabolomics of Serum and Feces in Weaned Piglets Challenged by Escherichia coli - Wang, Dingfa; Zhou, Luli; Zhou, Hanlin; Hou, Guanyu (Frontiers in Veterinary Science, 2021)
The effects of dietary supplementation with guava leaf extracts (GE) on intestinal barrier function and its modulation of serum and fecal metabolic changes in weaned piglets challenged by enterotoxigenic Escherichia coli (ETEC) were investigated. Fifty weaned piglets (Duroc × Yorkshire × Landrace) from 5 pens (2 piglets per pen) were randomly divided into five groups: blank control group (BC), negative control group (NC), or those supplemented with 50 mg kg-1 (S50), 100 mg kg-1 (S100), or 200 (S200) mg kg-1 diet GE, respectively. On day 4, all piglets (except for BC) were orally challenged with about 1.0 × 109 colony-forming units (CFU) enterotoxigenic ETEC. After 28-day trial, intestinal barrier function and metabolomics of serum and fecal were investigated. Results demonstrated that dietary supplementation with GE (50-200 mg kg-1) increased protein expression of intestinal tight junction proteins (ZO-1, Occludin, Claudin-1) (P < 0.05) and sodium hydrogen exchanger 3 (NHE3) (P < 0.05). Moreover, dietary supplementation with GE (50-200 mg kg-1) upregulated level of tetrahydrofolic acid (THF) and reversed higher level of nicotinamide-adenine dinucleotide phosphate (NADP) caused by ETEC in serum compared with NC group (P < 0.05), and enhanced antioxidant ability of piglets. In addition, dietary addition with GE (100 mg kg-1) reversed the lower level of L-pipecolic acid caused by ETEC in feces compared with NC group (P < 0.05), and decreased oxidative stress response of piglets. Collectively, dietary supplementation with 50-200 mg kg-1 GE exhibited positive effect on improving intestinal barrier function. Meanwhile, dietary addition with GE organized and redistributed energy resources through similar or dissimilar metabolic pathways, and finally enhanced antioxidant ability of piglets challenged by ETEC.